Amusements and modernizing discourse: Attempts to form a bourgeois culture in Lima (1890-1912) - Muñoz Cabrejo, Fanni (1997)
In this paper I will show how the transformations promoted by the State and a local elite in Lima at the end of the century are part of an ideal of modernity. This ideal, common in Latin American elites and under the protection of positivist ideas, was not only associated with material progress but was also accompanied by the need to create a modern national culture, for which values, customs and customs were promoted. according to the European way of life. What were the means with which they tried to impose this new lifestyle? An approach to the world of fun, of the entertainment spread by this elite suggests some analytical clues for understanding this experience of modernity.